PENGARUH PERMAINAN TRADISIONAL BEBENTENGAN DALAM MENINGKATKAN KETERAMPILAN SOSIAL KERJA SAMA - Zahra Fauziah Muyasyarah; Yusup, Rinaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social Social cooperation skills are important to develop in elementary school students because they relate to students’ ability to interact and collaborate with others. One activity that can be used to foster these skills is the traditional game of “bebentengan.” This study aims to determine the effect of the traditional game of “bebentengan” on the social cooperation skills of fourth-grade students at SDN Benteng 1. This study employed a quantitative approach using an experimental method and a One-Group Pretest-Posttest design involving 32 students. Data were collected through a 20-item questionnaire on social cooperation skills. The data were then analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Paired Sample T-Test, and the N-Gain. The results showed that the students’ average cooperative social skills score increased from 50.94 on the pretest to 69.16 on the posttest, representing an increase of 18.22 points. The results of the Paired-Sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. Meanwhile, the N-Gain analysis yielded an average value of 0.598, which falls into the moderate category according to Hake’s classification. The results indicate that the traditional game of bebentengan can enhance students’ social and collaborative skills and can be used as a learning activity that provides students with opportunities to interact and collaborate directly.